Testamento vital : uma análise sob a ótica da autonomia da vontade privada e dos direitos fundamentais - Pessoa, Conrado Falcon (2019)
The present dissertation analyzed the advanced directive of living will through the fundamental rights, as well as under the panorama of the autonomy of the private will. The study of the right to life in its twofold aspect and of the role of the dignity through the fundamental rights, analysing both as consequences and bases for the fundamental rights. Because of the lack of positivation of the instrument of the living will, its study based on some of the main rights with which it has a link, is of fundamental importance. This relevance is due to the fact that, based on this assessment, it facilitates the understanding of the instrument's reflexes, as well as the viability, or not, of its positivation in the Brazilian legal system. In addressing fundamental rights related to the living will, aspects were permeated about their compatibility with the Constitution. In the study of the autonomy of the private will, institutes of the Constitutional Civil Law were highlighted, analyzing personality rights and the capacity of the individual, these institutes being related to the end of a dignified life. In addition, the analysis in question attracted the exploration of several institutes of the Brazilian Law that had links with the instrument itself and with the rights explored in this research. Finally, it became possible to appreciate some reflexes that the living will and the advanced directives, from all the gradation generated by the study of fundamental rights and private autonomy, can generate in the private and public spheres. The study was essentially documentary and bibliographical, using, also, the qualitative method in the analysis of the information collected.